PERBEDAAN PENGARUH LATIHAN IMAGERY DAN TANPA LATIHAN IMAGERY TERHADAP KETERAMPILAN SENAM DAN KEPERCAYAAN DIRI ATLET - Firmansyah, Helmy (Jorpres (Jurnal Olahraga Prestasi), 2011)
The background of this research was a lack of attention from coaches and athletes to impact of psychology aspect in increase of achievement. Psychological aspect had less attention in supporting improvement of achievement this thing is caused lack of knowledge of coaches about mental practice.This research had purpose in knowing the influence of imagery practice to the athlete's skill and self confidence, also the different influence between imagery practice and nonimagery practice to skill and self confidence. The research used experimental method with total population. Subject of the research was 60 athletes who consist of 12 PPLP gymnastic athletes (4 boys and 8 girls) and 48 gymnastic club athletes (18 boys and 20 girls). In this research, the sample divided into 2 groups, they are (1) Group A (imagery exercises), (2) Group B (non imagery exercises) as controlling group. However, group A had a treatment of imagery exercises and Group B had no treatment of imagery exercises at all. The research went on 6 weeks with 6 times practices every week.The result of the research showed that there was difference influence of exercises imagery and practice without imagery to gymnastic skill (Sig 0. 72 < 0.05). While difference influence of imagery and without imagery exercises to self confidence doesn't significant (Sig 0.027 > 0.05).Conclusion from this research is imagery exercises better compared to without imagery exercises to gymnastic skill, and there are no difference of influence imagery and without imagery exercises to self confidence. Keyword: Imagery Exercise, Gymnastics Skills, Self Confidence